PENGGUNAAN BAHASA OLEH K.H. ANWAR ZAHID DALAM CERAMAH AGAMA - Ema Yuniar; Bambang Wibisono; A. Erna Rochiyati S. (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2019)
Religious speech (Islam) is a form of oral language used by a preacher to preach or communicate public directly.The purpose of this study is to describe the use of language in religious lectures by K.H. Anwar Zahid, one of the well-known religious preachers in East Java, also described the factors why he chooses the language in his preaching. Data is obtained by listening technique by applying SLBC (simak libat bebas cakap) method. In this method the researchers only acts as an observer to their informants. They do not involve in a speech event even though in the language was being scrutinized. SBLC is used to listen to the language used in religious sermon by K.H. Anwar Zahid. The data are taken from You tube channel. We use extra lingual equivalent method to analyze the factors underlying the use of language in religious speeches by K.H. Anwar Zahid. The results showed that K.H. Anwar always did code-mixing events, never using a single language in his preaching. Factors behind his choosing language are place, audience or target audience.